Ongoing challenges in pulmonary fibrosis and insights from the nintedanib clinical programme - Valenzuela, Claudia; Torrisi, Sebastiano Emanuele; Kahn, Nicolas; Quaresma, Manuel; Stowasser, Susanne; Kreuter, Michael (Respiratory research, 2020)
The approvals of nintedanib and pirfenidone changed the treatment paradigm in idiopathic pulmonary fibrosis (IPF), and increased our understanding of the underlying disease mechanisms. Nonetheless, many challenges and unmet needs remain in the management of patients with IPF and other progressive fibrosing interstitial lung diseases.